Effect of intra vaginal progesterone pessaries and PMSG on fecundity rate in Malabari goats - SELVARAJU, M; KATHIRESAN, D; DEVANATHAN, T G (The Indian Journal of Animal Reproduction, 2023)
Oestrus was synchronized in Malabari goats using 45 mg Fluorogestone Acetate (FGA group; n=l4) or 60 mg MedroxyProgesterone Acetate (MAP group; n=l4) intra vaginal sponges or Controlled Internal Drug Release (CIDR group n=l2) devicecontaining 0.332 g natural progesterone. These intra vaginal sponges or devices were kept in situ for 18 days in all 3 groups and 600I.U. PMSG was administered intra muscularly to all the does at the time of sponge or CIDR removal. Breeding at induced oestrus wasdone by natural service or A.I. at 48 and 60 hours of sponge or CIDR removal. This study indicated that the fecundity in Malabarigoats could be improved and the incidences of twins and triplets could also be artificially increased by oestrus synchronizationprocedures.
Keywords: Progesterone pessaries; PMSG; FGA; MAP; CIDR; fecundity; goats